DILEMA SOSIAL DALAM THE SOCIAL DILEMMA Analisis Naratif atas Absennya Wawasan Kewargaan dalam Film The Social Dilemma - Wisnu Martha Adiputra (Jurnal Media dan Komunikasi Indonesia, 2022)
In general, the present narrative related to social media is its positive contribution to society. Social media is considered to contribute to a balanced relationship between the state, industry and citizens. Social media is assumed to improve a truly citizen-focused democracy. However, there is a different narrative in the docudrama film entitled The Social Dilemma. This film tells the story that social media as a product of a large information and communication technology company has a negative impact on society because their main goal is to make as much profit as possible. This research aims to analyze the narrative brought by a film that is different from the mainstream narrative. By using the narrative analysis method, it is found that this film has its own dilemma because in the end it is found in this film that civic insight tends to be inadequate or even absent from the narrative under study. It was found that there are four distinct social dilemmas in The Social Dilemma film, namely dilemmas in the aspects of character and characterization, series in the narrative, narrative plot, and the end point of the narrative. Real and fictional characters provide dilemmas for each element in the narrative that do not bring up civil society as the final form of citizens, the series in the narrative shows dilemmas in problem solving by citizens, linear and parallel plots create dilemmas in the narrative over the relationship between issues, the public, and citizens. The last dilemma is the presence of the state that replaces citizens as a dilemma at the end of the narrative, which shows the most unique dilemma of the content that actually provides an alternative narrative